2019
DOI: 10.1016/j.mex.2019.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Simplified setup for the vibration study of plates with simply-supported boundary conditions

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…These results have been instrumental in enhancing our understanding of the behavior of carbon steel under varying conditions and will undoubtedly serve as a valuable resource in future studies. The unilaterally reinforced perimeter conditions of P. Dumond et al [53] and K. Luo et al [54] have consistent results with both studies, as shown in Table 7. Determining the modal constraint frequency of a workpiece is a complex process that involves various factors.…”
supporting
confidence: 75%
“…These results have been instrumental in enhancing our understanding of the behavior of carbon steel under varying conditions and will undoubtedly serve as a valuable resource in future studies. The unilaterally reinforced perimeter conditions of P. Dumond et al [53] and K. Luo et al [54] have consistent results with both studies, as shown in Table 7. Determining the modal constraint frequency of a workpiece is a complex process that involves various factors.…”
supporting
confidence: 75%
“…As the mount and inner portion of the rim flexed upward, the outer portion of the rim flexed downward, and visa-versa. The characteristic oscillating central bulge in the backboard plate prominent in Figure 9 can also be found in [10][11][12][13].…”
Section: Methodsmentioning
confidence: 57%
“…The missed modes at 29 Hz and 49 Hz comprised the reciprocating rotational motion of the rim and mount about the Z-axis. The missed mode at 29 Hz had previously perplexed the authors' empirical modal analysis [9] as that was a common mode of vibrations in plates [11][12][13]. But we now understand that the lack of vertical motion of the rim in Figure 9 meant that any signal from the vertically-oriented accelerometer could have easily been overlooked as noise.…”
Section: Methodsmentioning
confidence: 93%
“…Looking beyond our first two modes of vibration, Dumond [5] provided valuable insight for modes 5-6, and the indicial notation used in this article was adopted for the quantification of plate-vibration-dominated modes 3-6. Irvine provided valuable insight for visualizing mode 4 [6] and dome-shaped mode 5 [7], especially since the plates that Irvine analyzed had the same aspect ratio of 1.5:1 as the basketball backboard in this study.…”
Section: Introductionmentioning
confidence: 99%